The Quality of Postpartum Care from the Perspective of the Recipients of the Comprehensive Health Center Service Using the SERVQUAL Pattern - Rahil Gholipour; Roonak Shahoei; Golbahar Ghaderkhani; Soma Zakaryaee; Soma Bahmani (Hamadan University of Medical Sciences, 2019)
Introduction: Postpartum delivery care, considered as one of the most important health care activities, is a very important factor in preventing unwanted maternal outcomes. This course is an ideal time to intervene in order to im-prove their health. Nowadays, the most important way to improve the quality of care is to evaluate the quali-ty. Therefore, the present study aimed to determine the quality of postpartum care from the viewpoint of re-cipients using the SERVQUAL pattern in Sanandaj comprehensive health centers in 2018. Methods: This descriptive-analytic study was conducted on 384 women who referred to the comprehensive health cen-ters of Sanandaj for postpartum care. Sampling was done by classification. Data was collected by the standard SERVQUAL questionnaire, which measures the quality gap in 5 dimensions of the service (tangibility, relia-bility, assurance, accountability and empathy) and measures 22 questions. Data was analyzed by SPSS 23 us-ing descriptive statistics, t-test and ANOVA. Results: In all five dimensions of quality of services there was a negative quality gap. The highest mean quality was in the reliability dimension (-1.82) and the lowest mean gap was related to the responsiveness dimension (-1.55). Also, there was no significant relationship between age, education level and number of children and quality gap (P> 0.05). Conclusion: The results showed that there is a gap between expectations and perception of service providers, and efforts to meet needs and achieve expectations are necessary.